T-helper cells and their cytokines in pathogenesis and treatment of asthma - Ji, Tingfen; Li, Hequan (Frontiers in Immunology, 2023)
Prosperous advances in understanding the cellular and molecular mechanisms of chronic inflammation and airway remodeling in asthma have been made over the past several decades. Asthma is a chronic inflammatory disease of the airways characterized by reversible airway obstruction that is self-resolving or remits with treatment. Around half of asthma patients are "Type-2-high" asthma with overexpression of type 2 inflammatory pathways and elevated type 2 cytokines. When stimulated by allergens, airway epithelial cells secrete IL-25, IL-33, and TSLP to derive a Th2 immune response. First ILC2 followed by Th2 cells produces a series of cytokines such as IL-4, IL-5, and IL-13. TFH cells control IgE synthesis by secreting IL-4 to allergen-specific B cells. IL-5 promotes eosinophil inflammation, while IL-13 and IL-4 are involved in goblet cell metaplasia and bronchial hyperresponsiveness. Currently, "Type-2 low" asthma is defined as asthma with low levels of T2 biomarkers due to the lack of reliable biomarkers, which is associated with other Th cells. Th1 and Th17 are capable of producing cytokines that recruit neutrophils, such as IFN-γ and IL-17, to participate in the development of "Type-2-low" asthma. Precision medicine targeting Th cells and related cytokines is essential in the management of asthma aiming at the more appropriate patient selection and better treatment response. In this review, we sort out the pathogenesis of Th cells in asthma and summarize the therapeutic approaches involved as well as potential research directions.